First estimates of the fundamental parameters of three Large Magellanic Cloud clusters - Piatti, Andres Eduardo (2011)
As part of an ongoing project to investigate the cluster formation and chemical evolution history in the Large Magellanic Cloud (LMC), we have used the CTIO 0.9 m telescope to obtain CCD imaging in the Washington system of NGC 2161, SL 874, and KMHK 1719—three unstudied star clusters located in the outer region of the LMC. We measured T1 magnitudes and C T1 colors for a total of 9611 stars distributed throughout cluster areas of 13:6 × 13:6 arcmin2. Cluster radii were estimated from star counts distributed throughout the entire observed fields. Careful attention was paid to setting apart the cluster and field star distributions so that statistically cleaned color-magnitude diagrams (CMDs) were obtained. Based on the best fits of isochrones computed by the Padova group to the (T1, C T1) CMDs, the δT1 index, and the standard giant branch procedure, ages and metallicities were derived for the three clusters. The different methods for both age and metallicity determination are in good agreement. The three clusters were found to be of intermediate-age (∼1 Gyr) and relatively metal-poor (½Fe=H ∼ 0:7 dex). By combining the current results with others available in the literature, a total sample of 45 well-known LMC clusters older than 1 Gyr was compiled. By adopting an age interval varying in terms of age according to a logarithmic law, we built the cluster age histogram, which statistically represents the intermediate-age and old stellar populations in the LMC. Two main cluster formation episodes that peaked at t ∼ 2 and ∼14 Gyr were detected. The present cluster age distribution was compared with star formation rates that were analytically derived in previous studies.